Consideration of the effect of manufacturing deviations from the shape of a multistage axial compressor - A. S. Zolotukhin; E. I. Davletgareeva; F. A. Malyshev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper presents the results of influence for manufacturing deviations from the shape of the flow part – cavities obtained during the refinement of the material part of the multistage axial compressor GTE-65.1. An approach to the mathematical description of cavities is described, consisting of four steps. This approach allows us to gradually determine the influence of the deviation on the characteristics of the compressor. For each of the four steps the integral characteristics of the compressor deviations in efficiency and the total pressure ratio are compared to the base geometry. The change in the stability of the compressor is analyzed, taking into account the cavities under consideration. The analysis of changes in the parameters of the compressor stages is carried out.